Shifting Local Islamic Cultural Values ​​in the Archipelago - Emi Nuraemi; Lina Pusvisasari; Fatma Husna Haibah Nurulloh; Ingeu Siti Aisyah (al-Wadhih: Journal of Islamic History and Civilization, 2025)
This research discusses the shift of local Islamic cultural values in Indonesia due to the influence of globalization and modernization. Local Islamic traditions influenced by the Wali Songo show a harmonious blend of Islamic teachings and local culture. However, globalization has caused these values to erode and affect people's religious identity. This research uses a qualitative approach with a literature analysis method. The results show that the preservation of local Islamic values requires synergy between the government, scholars, and the community.